Mediating politics newspapers, radio, television and the Internet - Washbourne, Neil (Maidenhead, England Open University Press, 2010)
Outlines the ways in which political messages are formulated, broadcast, and received, as well as examining the ways in which the media and political organizations are linked to one another. Analyzes the relationship between the media and globalization, de-regulation of the media, and apathy of audiences. Illustrated throughout with case studies from the US, UK, and across the world, the book also explores celebrity politicians, how different national media systems encourage (or discourage) political engagement, how young people engage with the media and politics, and how the Internet has affected the organization of politics and news media.
Includes bibliographical references (p. [151]-172) and index
Keywords: Mass media -- Political aspects; Internet -- Political aspects; Mass media -- Political aspects -- Case studies; Internet -- Political aspects -- Case studies